2019
DOI: 10.1001/jamanetworkopen.2019.18287
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians’ Experiences With and Strategies for Managing Electronic Messages

Abstract: IMPORTANCE The increasing use of electronic communications has enhanced access to physicians for patients and clinical staff. Primary care physicians (PCPs) have anecdotally identified electronic inbox management as a new source of work-related stress. OBJECTIVES To describe PCPs' experiences managing their electronic inboxes and to characterize the array of management strategies developed by individual physicians and practice groups. DESIGN, SETTING, AND PARTICIPANTS This qualitative study was conducted in 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…Several studies captured the apprehensions of providers due to secure messaging [ 122 , 124 ]. In these studies, health care providers articulated the lack of clarity around appropriate ways to communicate via a portal as patients had expectations to receive immediate responses to their inquires [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies captured the apprehensions of providers due to secure messaging [ 122 , 124 ]. In these studies, health care providers articulated the lack of clarity around appropriate ways to communicate via a portal as patients had expectations to receive immediate responses to their inquires [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, health care providers articulated the lack of clarity around appropriate ways to communicate via a portal as patients had expectations to receive immediate responses to their inquires [ 124 ]. Lieu et al [ 122 ] reported provider anxiety because of the lack of volume restrictions on electronic messages and their coping strategies to timing their responses to patient messages. Another study found that messaging increased work outside normal work hours [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with a prior qualitative study that found that some departments in this setting had approaches to aid PCPs with inbox management, such as teams to help with messages or scheduled time for inbox management. 2 …”
Section: Discussionmentioning
confidence: 99%
“…Primary care physicians (PCPs) have identified the inbox within the electronic health record (EHR) as a source of work-related stress. 1 , 2 , 3 , 4 One possible reason is that it adds to the multiple demands that compete for PCPs’ attention during the workday. Given that PCPs spend large portions of their time using EHRs, 5 , 6 , 7 , 8 electronic inbox work could be associated with many switches in attention when processing messages amid patient visits and other clinical responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 18 studies [40][41][42]50,51,54,55,57,64,66,82,87,[120][121][122][123][124][125] and 3 reports [114,126,127] addressed the health care workforce perspective through various methods (mixed methods, n=7; prospective observational, n=2; qualitative, n=6; and surveys, n=6), with a focus on conducting formative and process evaluations. A total of 11 studies were conducted in the United States, 5 in Sweden, 4 in Canada, and 1 in China.…”
Section: Health Care Workforcementioning
confidence: 99%